APPLICATION OF AUGMENTED REALITY LEARNING MEDIA IN COVALENT BOND FORMATION BASED ON VALENCE BOND THEORY TO IMPROVE SUBMICROSCOPIC REPRESENTATION ABILITY - Elsa Awalia Lesmana; Ida Farida; Ferli Septi Irwansyah (UIN Sunan Gunung Djati Bandung, 2021)
This study aimed to apply Augmented Reality learning media to improve the ability of submicroscopic representation in the material of covalent bond formation based on valence bond theory. Determination of the sample used the pre-experimental method. This research was conducted in the fourth semester using a scientific learning model based on submicroscopic representation. Data collection techniques used the pre-test and post-test questions with 20 multiple choice questions through the LMS (Learning Management System) application, observation sheets and student worksheets. The results of the data analysis showed an increase in learning using AR media. Based on the t test results of pre-test and post-test through the SPSS IBM 23 output obtained t test synignification of 0.000 <0.05, showed that Ho was rejected and Ha was accepted and could be categorized as moderate with the N- gain value of 0.45.